STRUKTUR VEGETASI MANGROVE DI DESA POPALO KABUPATEN GORANTALO UTARA - Nurlena Duhe; Marini Susanti Hamidun; Abubakar Sidik Katili; Febriyanti; 5Ilyas H. Husain; Waode Faridawaty (Pojok Publisher, 2025)
This study focuses on observing the structure of mangrove vegetation in Popalo Village, North Gorontalo Regency. Scientists found that the condition of mangrove forests in the area is not uniform, with some areas still well maintained, especially near rivers and beaches, while other areas, especially near settlements, have been damaged due to land conversion into ponds. This type of research is descriptive quantitative using a survey method. The most dominant type of mangrove found is Rhizophora. In addition, this study also shows that environmental factors such as temperature, air acidity, and salt levels greatly affect the growth and development of mangroves. Overall, the results of this study highlight the importance of better conservation and management efforts for mangrove forests in Popalo Village to maintain the sustainability of coastal ecosystems.